Ultrasonic-Assisted Conversion of Micrometer-Sized BiI3 into BiOI Nanoflakes for Photocatalytic Applications - Das, Tushar Kanti; Jesionek, Marcin; Mistewicz, Krystian; Nowacki, Bartłomiej; Kępińska, Mirosława; Zubko, Maciej; Godzierz, Marcin; Gawron, Anna (International journal of molecular sciences, 2024)
This work describes a novel method for converting bismuth triiodide (BiI3) microplates into bismuth oxyiodide (BiOI) nanoflakes under ultrasonic irradiation. To produce BiOI nanoflakes with a high yield and high purity, the conversion process was carefully adjusted. Rapid reaction kinetics and increased mass transfer are benefits of the ultrasonic-assisted approach that result in well-defined converted BiOI nanostructures with superior characteristics. The produced BiOI nanoflakes were examined utilizing a range of analytical methods, such as Transmission Electron Microscopy (TEM), scanning electron microscopy (SEM) and X-ray diffraction (XRD). The progress in the ultrasonic conversion process with time was monitored through diffuse reflectance spectroscopy (DRS). The outcomes demonstrated the effective conversion of BiI3 microplates into crystalline, homogeneous, high-surface-area BiOI nanoflakes. Additionally, the degradation of organic dyes (methylene blue) under ultraviolet (UV) light irradiation was used to assess the photocatalytic efficacy of the produced BiOI nanoflakes. Because of their distinct morphology and electrical structure, the BiOI nanoflakes remarkably demonstrated remarkable photocatalytic activity, outperforming traditional photocatalysts. The ability of BiOI nanoflakes to effectively separate and utilize visible light photons makes them a viable option for environmental remediation applications. This work not only shows the promise of BiOI nanoflakes for sustainable photocatalytic applications but also demonstrates a simple and scalable approach to their manufacturing. The knowledge gathered from this work opens up new avenues for investigating ultrasonic-assisted techniques for creating sophisticated nanomaterials with customized characteristics for a range of technological uses.
Keywords: bismuth oxyiodide; ultrazvukové vlny; katalýza; Ultrasonics; bismuth triiodide; ultrafialové záření; jodidy; Ultrasonic Waves; nanostruktury; X-Ray Diffraction; Catalysis; Methylene Blue; Iodides; Nanostructures; ultrasonic irradiation; Photochemical Processes; bismut; ultrazvuk; fotochemické procesy; Ultraviolet Rays; methylene blue; Bismuth; difrakce rentgenového záření; methylenová modř; photocatalytic